Relationship between Drugs Use and Sexual Risk Behaviors among Senior High School Students - Herijanto, Yola Yuniaarti; Saputra, Lucky; Dhamayanti, Meita (Althea Medical Journal, 2017)
Background: Drugs use and risky sexual behavior among teenager are some of crucial problems arising in Indonesia. Statistic showed that there is an increasing prevalence in drugs use and risky sexual behavior among teenagers. This study was conducted to analyze the relationship between drugs use and risky sexual behaviors among high school students. Methods: An analytic study involving 432 students in 5 state high schools located in Kerees region Bandung, West Java, Indonesia, was carried out in 2013. The region was chosen due the high prevalence ofÂ  substance abuse. The inclusion criteria were every high school students in the Karees region. The exclusion criteria were the students who refused to participate in the study, did not come when the sample was taken, and did not fill the questionnaire completely. The instruments used for the study were questionnaires with cross-sectional technique. Furthermore, the questionnaire used for analyzing drugs use was Addiction Severity Index-Lite Version (ASI-lite) questionnaire; with additional questionnaire to analyze risky sexual behaviors.Results: Out of 432 students, 23.8% students already engaged to one or more risky sexual behavior. Among all respondents, the prevalence of students who had already done kissing was 22.7%, necking 9.3%, petting 7.2% and sexual intercourse 1.2%. Illegal drugs had been used at least once by 21.8% students. According to Chi-square test, drugs use and risky sexual behavior were related.Conclusions:The prevalence of both drugs use and risky sexual behaviors are high and students who use drugs are more prone to do risky sexual behavior. [AMJ.2017;4(1):125â8]Â DOI:Â 10.15850/amj.v4n1.1032